2015
DOI: 10.1002/yea.3069
|View full text |Cite
|
Sign up to set email alerts
|

Puromycin‐ and methotrexate‐resistance cassettes and optimized Cre‐recombinase expression plasmids for use in yeast

Abstract: Here we expand the set of tools for genetically manipulating Saccharomyces cerevisiae. We show that puromycin-resistance can be achieved in yeast through expression of a bacterial puromycin-resistance gene optimized to the yeast codon bias, which in turn serves as an easy to use dominant genetic marker suitable for gene disruption. We have constructed a similar DNA cassette expressing yeast codon-optimized mutant human dihydrofolate reductase (DHFR) that confers resistance to methotrexate and can also be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Standard yeast extract peptone dextrose (YPD)-rich medium (2% glucose, 2% peptone, and 1% yeast extract) and synthetic complete (SC) minimal medium (2% glucose, yeast nitrogen base; Research Products International) lacking appropriate amino acids and bases for plasmid selection were used. Geneticin (G418), used at a concentration of 250 µg/ml, and methotrexate (Sigma-Aldrich), used as described ( MacDonald and Piper, 2015 ), were used for selection of yeast integrant strains. For genetic screening, the MAT α haploid deletion library ( Winzeler et al, 1999 ) was purchased from Dharmacon.…”
Section: Methodsmentioning
confidence: 99%
“…Standard yeast extract peptone dextrose (YPD)-rich medium (2% glucose, 2% peptone, and 1% yeast extract) and synthetic complete (SC) minimal medium (2% glucose, yeast nitrogen base; Research Products International) lacking appropriate amino acids and bases for plasmid selection were used. Geneticin (G418), used at a concentration of 250 µg/ml, and methotrexate (Sigma-Aldrich), used as described ( MacDonald and Piper, 2015 ), were used for selection of yeast integrant strains. For genetic screening, the MAT α haploid deletion library ( Winzeler et al, 1999 ) was purchased from Dharmacon.…”
Section: Methodsmentioning
confidence: 99%
“…It was long believed that yeast shows little uptake of puromycin and are also insensitive to its effects, with the only applicability being in spheroplasts [ 16 , 17 ]. However, in recent years it was found that intact Saccharomyces cerevisiae indeed showed growth inhibition when treated with puromycin, just at much higher concentrations than those necessary for mammalian cells [ 18 , 19 ]. Approaches aimed at increasing the susceptibility of S. cerevisiae to puromycin focused on disturbing cell membrane integrity, either by knocking out a component of the ergosterol pathway, or by targeting the pleitropic drug response [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years it was found that intact Saccharomyces cerevisiae indeed showed growth inhibition when treated with puromycin, just at much higher concentrations than those necessary for mammalian cells [ 18 , 19 ]. Approaches aimed at increasing the susceptibility of S. cerevisiae to puromycin focused on disturbing cell membrane integrity, either by knocking out a component of the ergosterol pathway, or by targeting the pleitropic drug response [ 19 , 20 ]. Using such engineered strains (EPP: erg6 Δ, pdr1 Δ and pdr3 Δ) made an in vivo incorporation of puromycin into S. cerevisiae proteins possible [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For glucose-starvation experiments, rich and minimal media were supplemented with 2% raffinose instead of glucose, but were otherwise identical. Geneticin (Formedium), used at a concentration of 250 μg/ml in rich media, and methotrexate (Alfa Aesar), used at a working concentration of 20 mM, were prepared in SC minimal medium as described previously ( MacDonald and Piper, 2015 ). Expression of proteins from the CUP1 promoter was achieved by addition of 50–100 µM CuCl 2 to the medium for at least 1 h prior to downstream analysis.…”
Section: Methodsmentioning
confidence: 99%